Revolusi Digital Perbankan Syariah: Mendorong Inovasi Keuangan Islam di Indonesia - Wahab, Fatkhul; Ihsan, Moh. (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
The digital revolution in the Islamic banking sector in Indonesia marks a pivotal transformation from conventional service models to technology-driven, Sharia-compliant financial solutions. This article explores how digital innovation fosters the development of Islamic financial services in Indonesia. Utilizing a qualitative-descriptive approach, this research examines the integration of digital platforms, including mobile banking, fintech sharia, and blockchain, in creating inclusive and transparent Islamic financial ecosystems. The study also highlights the role of regulatory support from financial authorities in accelerating digital adaptation while maintaining Sharia compliance. Key findings indicate that digital transformation not only enhances service efficiency but also expands access to Sharia-compliant finance, particularly for the digitally literate younger generation. However, challenges remain in terms of infrastructure gaps, digital literacy, and the need for standardized Sharia governance frameworks in digital platforms. This paper concludes that the synergy between technology and Islamic values provides a strategic opportunity for Indonesia to lead in global Islamic financial innovation.